Seroprevalence of SARS CoV-2 among children after the second surge (June 2021) in a rural district of South India: Findings and lessons from a population-based survey - George, Carolin Elizabeth; Inbaraj, Leeberk Raja; Rajukutty, Shon; Joan, Roshni Florina; Muthuraj, Sangeetha; Chandrasingh, Sindhulina (Frontiers in Pediatrics, 2022)
Objective To determine the seroprevalence of SARS COV 2 among children in the Bangalore Rural district. Methods We conducted a cross-sectional study after the second surge of COVID-19 from 14 June to 13 July 2021 and recruited 412 children through house-to-house visits from four villages in a rural district. We administered a questionnaire to collect demographics and details of COVID-19 infection and used the ABCHEK Antibody Card test (NuLifecare, India) which is an ICMR-approved test for detecting antibodies (IgG & IgM) by immunochromatography using the finger prick method. We used Statistical Package for the Social Sciences version 20.0 for analysis. Results Our participants had an age group ranging from 11 months to 18 years. There was an almost equal distribution of boys (48.3%) and girls (51.7%). We estimated seroprevalence of 45.9 % (95% CI: 41-50.8) among children. Seroprevalence was significantly associated with a history of symptoms suggestive of COVID-19 in the past, the seropositive status of the parents, and any other family members being tested positive. Age and gender of the child, education and occupation of the parents were not associated with the seropositivity status of the child. Conclusion Seroprevalence of COVID-19 among children corresponds to adult seroprevalence during the same time interval. This knowledge can be of practical application where adult prevalence is documented. Unvaccinated children in low-resource settings need special attention with respect to monitoring for new mutations as well as managing endemic needs.